Oral anticoagulation use by patients with atrial fibrillation in Germany - Wilke, Thomas; Groth, Antje; Mueller, Sabrina; Pfannkuche, Matthias; Verheyen, Frank; Linder, Roland; Maywald, Ulf; Kohlmann, Thomas; Feng, You-Shan; Breithardt, Günter; Bauersachs, Rupert (Thrombosis and Haemostasis, 2012)
Atrial fibrillation (AF) is the most common significant cardiac rhythm disorder. Oral anticoagulation (OAC) is recommended by guidelines in the presence of a moderate to high risk of stroke. Based on an analysis of claims-based data, the aim of this contribution is to quantify the stroke-risk dependent OAC utilisation profile of German AF patients as well as the possible causes and the associated clinical outcomes of OAC under-use. Our data set was derived from two large mandatory German medical insurance funds. Risk stratification of patients was based on the CHADS2-score and the CHA2DS2-VASc-score. Two different scenarios were constructed to deal with factors potentially disfavouring OAC use. Causes of OAC under-use and its clinical consequences were analysed using multivariate analysis. Observation year was 2008. A total of 183,448 AF patients met the inclusion criteria. This represents an AF prevalence of 2.21%. The average CHADS2-score was 2.8 (CHA2DS2-VASc-score: 4.3). On between 40.5 and 48.7% of the observed patient-days, there was no antithrombotic protection by OAC, other anticoagulants or aspirin. Older female patients with a high number of comorbidities had a higher risk of OAC under-use. Patients who had already experienced a thromboembolic event had a lower risk of OAC under-use. In the observation year, 3,367 patients experienced a stroke (incidence rate 1.8%). In our multi-level Poisson random effects estimate, OAC use decreases the stroke rate by almost 80% (IRR 0.236). In conclusion, OAC under-use is widespread in the German market. It is associated with severe clinical consequences.
Keywords: Vitamin K-dependent factors; antiplatelet agents; management of disease